2018
DOI: 10.1002/adma.201707073
|View full text |Cite
|
Sign up to set email alerts
|

Functional Enzyme Mimics for Oxidative Halogenation Reactions that Combat Biofilm Formation

Abstract: Transition-metal oxide nanoparticles and molecular coordination compounds are highlighted as functional mimics of halogenating enzymes. These enzymes are involved in halometabolite biosynthesis. Their activity is based upon the formation of hypohalous acids from halides and hydrogen peroxide or oxygen, which form bioactive secondary metabolites of microbial origin with strong antibacterial and antifungal activities in follow-up reactions. Therefore, enzyme mimics and halogenating enzymes may be valuable tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 332 publications
(493 reference statements)
0
60
0
Order By: Relevance
“…Therefore, great efforts have been devoted to developing alternative antibacterial materials in recent years . Particularly, inspired by natural enzymes for damaging bacteria through catalyzing the production of harmful reactive oxygen species (ROS), researchers diverted their attention to the construction of artificial enzymes with the functions of natural enzymes to combat bacteria . Different from high‐cost and instable natural enzymes, nanozymes are generally facile‐preparation and stable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, great efforts have been devoted to developing alternative antibacterial materials in recent years . Particularly, inspired by natural enzymes for damaging bacteria through catalyzing the production of harmful reactive oxygen species (ROS), researchers diverted their attention to the construction of artificial enzymes with the functions of natural enzymes to combat bacteria . Different from high‐cost and instable natural enzymes, nanozymes are generally facile‐preparation and stable.…”
Section: Introductionmentioning
confidence: 99%
“…They can imitate the extraordinary activities of natural enzymes in biocatalytic chemistry and overcome their shortcomings like poor stability and high cost. [ 2–5 ] Among various kinds of nanozymes, [ 6–14 ] carbon‐based nanozymes attracts enormous attention due to their unique physiochemical properties, [ 13,14 ] higher operational stability, and lower cost. [ 15,16 ] Up to now, carbon‐based nanozymes have shown the excellent capability of mimicking enzyme‐like activities.…”
Section: Methodsmentioning
confidence: 99%
“…Among various kinds of nanozymes, [6][7][8][9][10][11][12][13][14] carbon-based nanozymes attracts enormous attention due to their unique physiochemical properties, [13,14] higher operational stability, and lower cost. [15,16] Up to now, carbon-based nanozymes have shown the excellent capability of mimicking enzymelike activities.…”
mentioning
confidence: 99%
“…In addition, it could be demonstrated that the anodized tin surfaces present amphiphilic properties by switching from a hydrophobic to a hydrophilic behavior under UV light. This discovery could lead to the development of new protective, antibacterial and antifouling coatings by a simple anodization of oriented tin foils.…”
Section: Discussionmentioning
confidence: 99%